Associations between chemosensory function, sweet taste preference, and the previous night's sleep in non-obese males. (July 2019) - Szczygiel, Edward J.; Cho, Sungeun; Snyder, Margaret K.; Tucker, Robin M.
Highlights: Participants with a short night's sleep preferred sweeter solutions. Total and REM sleep duration was inversely associated with sweet taste preference. Males and females showed similar inverse sleep-taste preference associations. Abstract: There is a growing body of evidence suggesting that sleep influences chemosensory perception. Males and females differ in neural responses to chemosensory function as well as average sleep duration, suggesting the possibility of sex differences regarding relationships between sleep and chemosensory perception. Therefore, the primary objective of this study was to characterize relationships between sleep and chemosensory function in males. Secondary analyses compared responses to females from an earlier study. A total of 51 non-obese (BMI < 30.0 kg/m 2 ) male participants completed testing. Sleep was measured using a single-channel (A1 –A2 ) electroencephalogram (Zmachine) and next day sensory function, including sweet taste threshold, preferred sweet taste concentration, olfactory threshold, olfactory identification ability, and odor pleasantness ratings, were evaluated. After correction for false discovery rate (FDR), preferred sweet taste concentration was negatively associated with total sleep time (TST) (P = 0.0444), rapid eye movement (REM) sleep (P = 0.0060), and the sum of REM and SWS (P = 0.0060). Odor identification ability was positively associated with TST (P = 0.0187) and REM sleep duration (P = 0.0424), but these findings did not survive FDR correction (P > 0.05). Participants grouped into shorter sleep groups and low REM + SWS preferred significantly greater sucrose concentrations than those in longer and high REM + SWS groups (P = 0.0420, 0.0039, respectively). Multiple regression analysis indicated that REM alone was the best predictor of sweet taste preference, and that TST alone was the best predictor of odor identification score. While the best predictors for preferred sweet taste concentration differed between males and females, no differences in preferred sucrose concentration were observed.